Bands in crisis contexts. The company Aguas de Mondariz and its response to the crisis of cucumbers. - Vázquez Gestal, Montse; Fernández Souto, Ana Belén (Historia y Comunicación Social, 2014)
Institutional crises entail consequences in practically all areas of life, including the advertising. In this case, we highlight the response of the Spanish advertising brands, specifically Aguas de Mondariz, during the crisis of the cucumbers in the year 2011, which put into question the quality of Spanish products due to the accusations of the German authorities.